2018
DOI: 10.1371/journal.ppat.1007094
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes InlP interacts with afadin and facilitates basement membrane crossing

Abstract: During pregnancy, the placenta protects the fetus against the maternal immune response, as well as bacterial and viral pathogens. Bacterial pathogens that have evolved specific mechanisms of breaching this barrier, such as Listeria monocytogenes, present a unique opportunity for learning how the placenta carries out its protective function. We previously identified the L. monocytogenes protein Internalin P (InlP) as a secreted virulence factor critical for placental infection. Here, we show that InlP, but not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 68 publications
0
60
0
1
Order By: Relevance
“…One potential explanation may pertain to the L. monocytogenes internalin family of proteins which are involved in several stages of its infection cycle. Cell surface internalin A (InlA) and InlB control initial bacterial invasion into cells (77,78; see also reference 79 for a review), whereas secreted internalin C (InlC) and InlP have been shown to promote bacterial cell-to-cell and cell-to-basement membrane transfer, respectively (80,81). Consequently, future investigations into the L. monocytogenes infection cycle should focus on evaluating whether or not these bacterial components are also involved in the caveolin-mediated engulfment of membrane protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation may pertain to the L. monocytogenes internalin family of proteins which are involved in several stages of its infection cycle. Cell surface internalin A (InlA) and InlB control initial bacterial invasion into cells (77,78; see also reference 79 for a review), whereas secreted internalin C (InlC) and InlP have been shown to promote bacterial cell-to-cell and cell-to-basement membrane transfer, respectively (80,81). Consequently, future investigations into the L. monocytogenes infection cycle should focus on evaluating whether or not these bacterial components are also involved in the caveolin-mediated engulfment of membrane protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…Both of them were found to be required for invasion into multiple different cell types, initiating a zipper-type endocytosis [11,30,31]. In addition to InlA and InlB, there are other Inl family members addressed in the literature-for some of them, host cell interaction partners and functions have been described (InlC, InlF, InlK and InlP), while the role of the others is suggested on the basis of available data but not yet fully confirmed (InlH, InlJ and InlL) [19,21,26,[32][33][34][35].…”
Section: Internalinsmentioning
confidence: 99%
“…Similarly, we showed that when L.m. crosses through basement membranes such as those of the placenta, it secretes the InlP toxin which leads to a weakening of the tensional forces between host epithelial cells and their extracellular matrix, thus facilitating apico-basal bacterial spread 4 . Rickettsia parkeri, a bacterial pathogen that undergoes actin based motility like L.m., powers its intracellular spread by reducing intercellular tension between host epithelial cells through secretion of the effector protein Sca4 that disrupts cell-cell junctions 1 .…”
Section: Rajabian Et Al Showed That Secretedmentioning
confidence: 99%
“…The biomechanical interactions between host cells and bacterial pathogens are dictated by both the pathogen and the host. It has been previously shown that there are ways through which intracellular pathogens can manipulate host cell functions, including host cell mechanotransduction, in order to spread more efficiently [1][2][3]…”
Section: Introductionmentioning
confidence: 99%